UPAYA PEMBERSIHAN SAMPAH RUANG ANGKASA SEBAGAI IMPLEMENTASI TANGGUNG JAWAB NEGARA TERHADAP PENANGANAN SAMPAH RUANG ANGKASA BERDASARKAN SPACE TREATY 1967 - Asyam Mulia Zhafran; Maria Maya Lestari; Ledy Diana (Lafadz Jaya Publisher, 2023)
Currently, activities in outer space are commonplace for both developed and developing countries. Technological developments affect the intensity of the country's activities in space. All human activities in outer space have been regulated in the 1967 space treaty. However, many launches have been carried out by countries in outer space, outer space has begun to be filled with various celestial bodies that used to be empty space. Pollution that occurs in outer space must be avoided, because it is detrimental to the earth's environment caused by the entry of material from outer space. The purpose of writing this thesis, namely, First, The reason for space trash must be cleaned up. Second, who is responsible for space junk. The type of research used in this research is normative legal research. Normative legal research, library materials are basic data in (science) research classified as secondary data. Based on this approach, the main material to be reviewed is secondary legal material. Which focuses on positive legal norms in the form of conventions, namely the 1967 Space Treaty on activities in space related to space and objects in space. From the research results, there are two main things that can be concluded. First, the public problem that often occurs in the space environment is the safety of astronauts and the safety of artificial satellites from debris that fills space. The thing that makes space trash a problem in the future for the world is because the amount continues to grow. If this increase continues, the density in certain orbital regions will one day be too high so that it will become a collision between two objects, so that the debris that occurs will trigger another collision. Second, the party that harms other countries, then the responsibility is borne by the owner of the satellite who has harmed another country, in other words, the direct actor, unless there is an agreement from the space subjects for the responsibility owned by the satellite.